ANALISIS PENGARUH PENANAMAN MODAL DALAM NEGERI DAN PENANAMAN MODAL ASING TERHADAP PERTUMBUHAN EKONOMI INKLUSIF DI INDONESIA - Shem Dwi Nehemia; Prasetyia, Ferry (Journal of Development Economic and Social Studies, 2023)
In the process of economic development, investment has an important role that makes the economy inseparable from investment activities. Empirical research on the relationship between investment and economic growth has been carried out a lot but only focuses on the effect on economic growth without presenting the perspective of equality and social welfare which can be seen from indicators of inclusive economic growth. This research will look at how domestic investment and foreign investment contribute to inclusive economic growth in Indonesia. Using data from 33 provinces in Indonesia from 2011 to 2018 which were processed using the Panel Data Regression method, it was found that foreign investment and domestic investment have a significant positive influence on inclusive economic growth in Indonesia. This result is also supported by the results of the control variable analysis, that a decrease in the open unemployment rate and an increase in government infrastructure spending will encourage inclusive growth in Indonesia.